The Study of Anxiety and Obsessive Disorder in Paula Hawkins’s into the Water: A Psychoanalytical Perspective - Anandia Treciel Vanessae Evato; Essy Syam; Qori Islami Aris (International Journal of English and Applied Linguistics (IJEAL), 2023)
Psychological problems in a person can be formed by many factors, including childhood and environmental experiences. Two of the many forms of psychological problems are anxiety and obsessive disorder. This research focuses to analyze the symptoms and effects of anxiety and obsessive disorders suffered by two main characters in Into the Water by Paula Hawkins using the theory of psychoanalysis. This research applies observation techniques in collecting the data from Into the Water novel. The result shows that both main characters experienced different symptoms that affected the way they live their lives. The anxiety in the first main character made it hard for him to differentiate the reality and myth. The obsession in the second main character made her became an intrusive person that interfered with other people’s private problems. This novel contains an ideology that a person may not seem as what he/she really is, as he/she might keep a secret that not everyone knows about.